Occurrence and antibiotic resistance of Salmonella sp. in mutton in wet markets in Serdang, Selangor - Hahlan, Muhamad Faizal (2015)
Salmonella sp. is the major pathogenic bacteria in humans as well as in animals, which causes acute gastroenteritis. Salmonellosis remains an important public health problem worldwide especially in developing countries. The objectives of the study were to determine the occurrence and antibiotic resistance patterns of Salmonella sp. isolated from mutton in wet market in Serdang, Selangor. A total of 30 random samples of mutton were collected from different butcher‟s shops in wet market and processed for isolation of Salmonella sp. by inoculating the samples into Rappaport-Vassiliadis (RV) Enrichment Broth (Oxoid) and later into Xylose lysine deoxycholate agar (XLD) and Briliant Green Agar (BGA) (Merck). All samples were found negative for Salmonella sp. This study highlights the mutton in wet market was free from Salmonella sp. and indicates that good hygienic practices in slaughterhouse was implemented. Consecutive studies with bigger sample sizes and covering all over Malaysia are warranted in future.